Metal (Ag/Ti)-Containing Hydrogenated Amorphous Carbon Nanocomposite Films with Enhanced Nanoscratch Resistance: Hybrid PECVD/PVD System and Microstructural Characteristics - Constantinou, Marios; Nikolaou, Petros; Koutsokeras, Loukas E.; Avgeropoulos, Apostolos; Moschovas, Dimitrios; Varotsis, Constantinos; Patsalas, Panos; Kelires, Pantelis C.; Constantinides, Georgios (My University, 2018)
This study aimed to develop hydrogenated amorphous carbon thin films with embedded metallic nanoparticles (a-C:H:Me) of controlled size and concentration. Towards this end, a novel hybrid deposition system is presented that uses a combination of Plasma Enhanced Chemical Vapor Deposition (PECVD) and Physical Vapor Deposition (PVD) technologies. The a-C:H matrix was deposited through the acceleration of carbon ions generated through a radio-frequency (RF) plasma source by cracking methane, whereas metallic nanoparticles were generated and deposited using terminated gas condensation (TGC) technology. The resulting material was a hydrogenated amorphous carbon film with controlled physical properties and evenly dispersed metallic nanoparticles (here Ag or Ti). The physical, chemical, morphological and mechanical characteristics of the films were investigated through X-ray reflectivity (XRR), Raman spectroscopy, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Transmission Electron Microscopy (TEM) and nanoscratch testing. The resulting amorphous carbon metal nanocomposite films (a-C:H:Ag and a-C:H:Ti) exhibited enhanced nanoscratch resistance (up to +50%) and low values of friction coefficient (<0.05), properties desirable for protective coatings and/or solid lubricant applications. The ability to form nanocomposite structures with tunable coating performance by potentially controlling the carbon bonding, hydrogen content, and the type/size/percent of metallic nanoparticles opens new avenues for a broad range of applications in which mechanical, physical, biological and/or combinatorial properties are required.
Keywords: Hybrid deposition system; Hydrogenated amorphous carbon films; Metallic nanoparticles; Nanocomposites; Nanoscratch